Peningkatan Self Efficacy pada Keluarga dengan Penyakit TB Paru melalui Terapi Psikoedukasi - Mochamad Heri; Putu Karisma Dewi; Gede Budi Widiarta; Made Martini (Jurnal Keperawatan Silampari, 2020)
This study aims to determine the effect of psychoeducation therapy on increasing self-efficacy in families with pulmonary TB disease at Kertha Usada General Hospital. Method: The research design used quasi-experimental with pre-post test with control group design. Results: The results showed the mean (mean) pre-test in the treatment group was 20.56 and in the control group was 21.04. The mean post-test mean in the treatment group was 31.51 and in the control group, the results were 30.57. Parametric test results using the Paired Sample T-test obtained p-value = (0,000) <Î± (0.05). Conclusion, there is an effect of psychoeducation therapy on increasing self-efficacy in families with Pulmonary of TB in Kertha Usada General Hospital. Keywords: Self-Efficacy, Family Psychoeducation Therapy, Tuberculosis